Assessment of students’ awareness of the national heritage (Case study: The preparatory year students at the University of Hail, Saudi Arabia) - Ahmed, Tarek Sayed Abdelazim (Cogent social sciences, 2017)
This study financed by the deanship of scientific research, Hail, University, Kingdom of Saudi Arabia aims to identify the degree of students’ awareness of the national heritage, to investigate the role school in raising awareness of the national heritage, to explore the degree of student satisfaction about that role played in addition to explore the impact of family in predicting the personal interest in the local heritage. A survey was conducted. About 250 questionnaires were distributed to random sample of students in the preparatory year in both in the males and females sections in cooperation with a number of teaching staff. Students who accepted and filled the questionnaires were 210 only, from which 32 were incomplete and thus eliminated from the study. As a result, 178 questionnaires were accepted for the purpose of the final analysis, representing a response rate of 87%. The results show that there is statistically significant contribution for familial interest in the national heritage in predicting the personal interest in local heritage. There is a statistically significant relationship between the place of residence and the perception of the level of awareness of the importance of the national heritage.